Ultralight self-charging triboelectric power paper with enhanced on-chip energy storage. (October 2022) - Ma, Weiting; Zhang, Maoqin; Yan, Wei; Zhu, Junbo; Liu, Jinzhang; Song, Weixing
Abstract: The ever-growing demands of loads and sensors of the Internet of things (IoT) in fifth generation (5 G) era spur innovation and development of environmentally sustainable power supplies. Herein, a self-charging power source based on paper is designed to harvest mechanical energy produced by hand movements and store them in micro-supercapacitors (MSCs). The triboelectric nanogenerator (TENG) with free-standing structure and the in-plane MSCs are integrated on one piece of paper, ruling out extra processes for wire bonding, circuit pad, and packaging, and thus effectively simplifying the self-powering system. The pencil lead material is drawn onto the paper to obtain in-plane interdigital MSCs and followed by surface functionalization with small pseudocapacitive aromatic molecules. High areal capacitance of 6.96 mAh g −1 cm −2 is achieved, which is about 6 times as much as pure pencil lead coating. As a proof-of-concept demonstration, some microelectronic devices like a wireless positioning sensor can be powered by our all-in-one self-charging power paper. Graphical Abstract: Triboelectric nanogenerator and pencil-drawn micro-supercapacitors are fabricated onto printing paper as the all-in-one thin and ultrathin self-charging power source with high voltage and frequency output. The pencil-drawn graphite functionalized with redox-active molecules could largely enhance the capacitance. ga1 Highlights: We present a concept that the self-charging power device can be made on a single piece of paper to generate and store electricity. 8-amino-2-nathol molecules are used to functionalize pencil-drawn electrodes, thus largely enhancing the capacitance due to added pseudocapacitance. Due to the ultrathin and flexible feature, the device can be used as a self-charging portable power source.